2015
DOI: 10.1118/1.4928397
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric commissioning and quality assurance of scanned ion beams at the Italian National Center for Oncological Hadrontherapy

Abstract: After successful dosimetric beam commissioning, quality assurance measurements performed during a 24-month period show very stable beam characteristics, which are therefore suitable for performing safe and accurate patient treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
161
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 134 publications
(172 citation statements)
references
References 60 publications
6
161
0
Order By: Relevance
“…The GAFCHROMIC (Ashland Inc., Cincinnati, OH, USA) EBT, EBT2 and EBT3 radiochromic film models, are widely used for particle beams commissioning and QA procedures . On the other hand it is non‐negligible the decrease in response due to the high specific ionization of ions at Bragg peak …”
Section: Detectors For Absorbed Dose In Nonreference Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GAFCHROMIC (Ashland Inc., Cincinnati, OH, USA) EBT, EBT2 and EBT3 radiochromic film models, are widely used for particle beams commissioning and QA procedures . On the other hand it is non‐negligible the decrease in response due to the high specific ionization of ions at Bragg peak …”
Section: Detectors For Absorbed Dose In Nonreference Conditionsmentioning
confidence: 99%
“…It has been shown that, especially at large depths, the Bragg peak chamber is not large enough to capture the whole laterally scattered dose . Therefore, the IDD curves have to be corrected by means of MC simulations …”
Section: Detectors For Absorbed Dose In Nonreference Conditionsmentioning
confidence: 99%
“…The work has been performed at CNAO (Centro Nazionale Adroterapia Oncologica, Pavia, Italy), 18 where the QA procedure is presently well established and based on Gafchromic films and a water phantom with a ionization chamber. 19 At CNAO hadrontherapy center a synchrotron based on the PIMMS (Proton-Ion Medical Machine Study) design 20 is used to deliver both proton and carbon ion beams. Patient treatments started with protons in September 2011 and with carbon ions in November 2012.…”
Section: Introductionmentioning
confidence: 99%
“…One of the available fixed horizontal beam lines was used. The GEMPix was placed inside a watertight PMMA box mounted on the 3D positioning system of the motorized water phantom routinely used for Quality Assurance (MP3-P, PTW Freiburg, Germany) [15]. In particular, the depth axis has a range of movement of more than 350 mm and a positioning reproducibility of ±0.1 mm.…”
Section: Experimental Setup At Cnaomentioning
confidence: 99%